Adherence to the treatment with oral antidiabetic medications in primary health care - Andréa Pereira da Silva; Braulio Vieira de Sousa Borges; José Cláudio Garcia Lira Neto; Fernanda Valéria Silva Dantas Avelino; Marta Maria Coelho Damasceno; Roberto Wagner Júnior Freire de Freitas (Rev Rene, 2015)
Objective: to assess the level of adherence to the drug treatment with oral antidiabetic medications in the primary health care network. Methods: analytical, quantitative study conducted with 63 patients with diabetes mellitus type 2 attended in three Basic Health Units. One used a form which included sociodemographic and clinical information related to treatment adherence, assessed through the Morisky-Green test. Results: it was found that 22.2% of the patients adhered to the treatment. There were no statistically significant correlations between adherence and sociodemographic and clinical variables. Conclusion: non-adherence was high, requiring intervention measures to correct the problem and to promote a better quality of life for patients with diabetes mellitus type 2.